Combustion characteristics and flame stability of linear esters of palmitic acid based on OH-PLIF technology. Issue 4 (August 2020) - Ni, Zi-hao; Li, Fa-she; Wang, Hua; Xu, Jian-xin; Yu, Wei; Ma, Xin; Jiang, Shang
Abstract: Experimental study on combustion characteristics and method for evaluating flame stability was carried out. Methyl palmitate, ethyl palmitate, propyl palmitate, butyl palmitate, and amyl palmitate were prepared using pyridine n-butyl bisulfate ionic liquid as catalyst in a self-designed reactor to catalyze esterification reaction of palmitic acid with methanol, ethanol, propanol, butanol, and pentanol, respectively. Combustion characteristics including the flame height, flame front area, and flame speed were analyzed; and OH-PLIF time-average total signal strength by the OH-PLIF technique and cold flow properties of linear-chain alkyl esters of palmitic acid were also studied. Image diagnosis was applied to the study of flame stability, and an image segmentation method using three color feature matrices of flame corresponding to the red, green, and blue components was proposed. A color was selected as the evaluation color and the iterative method was used to obtain the optimal threshold for the area where the flame was located. Each pixel in the matrix was compared with an optimal threshold, and the flame stability was evaluated by calculating the ratio variance under continuous conditions. The method is simple in operation, accurate in repeatability, less interfered, and provides some guidance for analysis and optimization of biodiesel combustion process. Highlights: Optimal conditions for linear-chain alkyl esters of palmitic acid were optimized. Combustion characteristics of the flame were measured and analyzed. Image diagnosis is applied to the study of flame stability.